Examining the issue of Indochina to understand Zhou Enlai’s neighborhood diplomacy - Qiu, Yang; Qin, Shan (Frontiers in Political Science, 2024)
In recent years, China’s neighboring environment has experienced profound changes, and China’s external security situation has been subject to a series of shocks. Against this background, China’s neighborhood diplomacy has become increasingly prominent. Indochina has been the focus of China’s neighborhood diplomacy since the Geneva Conference in 1954. Based on the declassified archives of Kissinger’s secret visit to China in 1971, this paper examines the issue of Indochina in the negotiations between Zhou Enlai and Kissinger. The aim is to offer a valuable historical experience for China’s neighborhood diplomacy of today and the way to manage and resolve strategic disputes in its neighboring area. The study finds that during the negotiations, Zhou took a clear stance on behalf of the Chinese government in expressing support for the struggle for the national independence of the Indochinese people. This reflects China’s unshakable commitment to the Five Principles of Peaceful Coexistence and support for the international justice of anti-aggression and anti-colonialism. Additionally, through his statements, Zhou has shown us the meaning of “amity, sincerity, mutual benefit, and inclusiveness (亲诚惠容 Qin Cheng Hui Rong)” in neighborhood diplomacy. All his efforts showed us how to effectively undertake neighborhood diplomacy, which is the essence of maintaining stability in China’s neighborhood.